2011
DOI: 10.1002/ange.201107404
|View full text |Cite
|
Sign up to set email alerts
|

Bridging between Organocatalysis and Biocatalysis: Asymmetric Addition of Acetaldehyde to β‐Nitrostyrenes Catalyzed by a Promiscuous Proline‐Based Tautomerase

Abstract: Nichtnatürliche Schönheit: Das Enzym 4‐Oxalocrotonat‐Tautomerase (4‐OT) zeigt eine nichtnatürliche Aktivität, indem es eine Michael‐Addition von Acetaldehyd an Nitrostyrol katalysiert. Die Reaktion verläuft wahrscheinlich über die Bildung eines Enamins zwischen dem N‐terminalen Prolin von 4‐OT und Acetaldehyd in Anlehnung an organokatalysierte Reaktionen. Eine hohe Stereoselektivität, geringe Katalysatormengen und Durchführbarkeit in Wasser zeichnen die Methode aus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…[10] We herein report that the enzyme 4-oxalocrotonate tautomerase (4-OT), [11] which carries a nucleophilic amino-terminal proline residue (Pro1), promiscuously catalyzes the asymmetric Michael-type addition of acetaldehyde to various aromatic and aliphatic nitroolefins yielding chiral g-nitroaldehydes (Scheme 1) with high stereoselectivities. In combination with our previously described 4-OT-catalyzed addition of linear aldehydes (acetaldehyde up to octanal) to trans-nitrostyrene, [12,13] this is the first example of enzymecatalyzed carbon-carbon bond-forming Michael-type additions that includes a range of linear aldehyde donors and a series of aromatic and aliphatic nitroolefin acceptors. [14] Furthermore, we found that catalytic activity of 4-OT is preserved in aqueous solvent systems containing up to 50 % (v/ v) of DMSO as co-solvent.…”
mentioning
confidence: 99%
“…[10] We herein report that the enzyme 4-oxalocrotonate tautomerase (4-OT), [11] which carries a nucleophilic amino-terminal proline residue (Pro1), promiscuously catalyzes the asymmetric Michael-type addition of acetaldehyde to various aromatic and aliphatic nitroolefins yielding chiral g-nitroaldehydes (Scheme 1) with high stereoselectivities. In combination with our previously described 4-OT-catalyzed addition of linear aldehydes (acetaldehyde up to octanal) to trans-nitrostyrene, [12,13] this is the first example of enzymecatalyzed carbon-carbon bond-forming Michael-type additions that includes a range of linear aldehyde donors and a series of aromatic and aliphatic nitroolefin acceptors. [14] Furthermore, we found that catalytic activity of 4-OT is preserved in aqueous solvent systems containing up to 50 % (v/ v) of DMSO as co-solvent.…”
mentioning
confidence: 99%
“…3) on the amino‐terminus of 4‐OT. This opens up new possibilities to study the catalytic importance of Pro‐1 in the recently discovered promiscuous C–C bond‐forming aldolase and ‘Michaelase’ activities of 4‐OT [10–14]. Labeling studies performed with the affinity probe 3BP demonstrate that pyroglutamate is less nucleophilic as proline in the active site of 4‐OT.…”
Section: Resultsmentioning
confidence: 98%
“…4‐OT is a member of the tautomerase superfamily, a group of homologous proteins characterized by a structural β‐α‐β‐fold and a catalytic amino‐terminal proline residue (Pro‐1) [4–6]. Pro‐1 was found to be crucial for both the natural and various promiscuous activities of the enzyme, which include the hydrolytic dehalogenation of trans ‐3‐chloroacrylic acid [7–9], the aldol condensation of acetaldehyde with benzaldehyde [10,11], the Michael‐type addition of linear aliphatic aldehydes to a variety of aliphatic and aromatic nitroolefins [12–14], and the cis – trans isomerization of nitrostyrene [15]. The chemical versatility of the amino‐terminal proline is the core of the catalytic diversity displayed by 4‐OT; Pro‐1 has been proposed to act as a general base (tautomerase activity), a general acid (dehalogenase activity), or as a nucleophile (aldol condensation, cis – trans isomerization, and Michael‐type additions) [7–16].…”
Section: Introductionmentioning
confidence: 99%
“…The enzyme 4‐oxalocrotonate tautomerase (4‐OT) naturally catalyzes the tautomerization of 2‐hydroxyhexa‐2,4‐dienedioate to 2‐oxohex‐3‐enedioate using the N‐terminal proline as key catalytic base . In addition, 4‐OT can promiscuously catalyze several carbon–carbon bond‐forming reactions, including Michael‐type additions and aldol condensations, employing Pro‐1 as a nucleophile . Most notably, 4‐OT can catalyze Michael‐type additions and aldol condensations using the highly reactive acetaldehyde ( 5 ) as a nucleophile (Scheme ).…”
Section: Introductionmentioning
confidence: 99%